Двойное лучепреломление рентгеновских лучей в нематических жидких кристаллах под воздействием внешнего электрического поля - Гаспарян, Л. Г.; Мкртчян, В. П.; Дадалян, Т. К.; Петросян, П. С. (Հայաստանի ԳԱԱ)
The effect of an external electric field on the refractive indices of ordinary and extraordinary waves is explored using method of the X-ray interferometer. The decrements of the nematic liquid crystal of type E7 were calculated for different values of the external electric field strength and it is established that with increasing electric field strength the values of the decrements of the ordinary and the extraordinary waves increases, tending to the same value.
Keywords: X-Ray; Physics